PELAKSANAAN REHABILITASI DAN PEMELIHARAAN RUAS JALAN HARGOMULYO â TEGALREJO KABUPATEN GUNUNGKIDUL DENGAN PERKERASAN KAKU (RIGID PAVEMENT) - , FRANSISCA YUNITA N ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pavement made in order to provide security and comfort for road users in the pass-traffic. Over time, a layer of pavement will be damaged. If damage occurs are left in the street for long periods, it will cause problems. Therefore, the need for rehabilitation and periodic maintenance of roads. Implementation of road rehabilitation and maintenance work carried out on roads Hargomulyo - Tegalrejo, which is located in Gedangsari, Gunungkidul. Rehabilitation and maintenance of roads using concrete rigid pavement with the quality of K-125. Work activities carried on along the road 555 m with workmanship for a period of 45 days. Work done using methods and equipment in accordance with the region's ability to stay abreast of guidance and technical requirements the implementation of concrete road construction has been set. During the concrete road work carried out is done to the concrete quality control is done. Tests performed include slump test values, testing the strength of concrete, and concrete thickness. From the results of tests performed Slump values obtained 7 cm, the characteristic compressive strength test results of concrete at 28 days of each specimen was 240.2 kg/cm2, 260.4 kg/cm2, 324.1 kg/cm2 , 291.5 kg/cm2, 312.2 kg/cm2, 295.3 kg/cm2, and the average results of flexural tensile strength of concrete at 4.01 MPa. Data from the test results, the concrete meets the requirements.